The Relationship Between Learning Discipline and IPAS Learning Outcomes of Fifth-Grade Students at SDI Sanging-Sanging, Gowa Regency - Rahmawati Rahmawati (International Journal of Elementary School Teacher, 2026)
This study analyzes the extent to which student discipline contributes to optimal learning outcomes in IPAS subjects at SDI Sanging-Sanging. The purpose of this study is to determine the relationship between discipline and learning outcomes and to describe the discipline and learning outcomes of fifth-grade IPAS students in Gowa Regency. This study uses a quantitative approach with a correlational descriptive method. The data sources used in data collection included primary and secondary data. Data collection was conducted through observation and questionnaire distribution, where the research instrument used in data collection employed the Likert scale method. Data analysis techniques used descriptive statistical analysis, research instrument testing, classical assumption testing, simple regression testing, and hypothesis testing. The results of the study indicate that there is a significant relationship between discipline and student learning outcomes. Thus, it can be concluded that the higher the level of student discipline, the higher the learning outcomes achieved by students at SDI Sanging-Sanging, Gowa Regency.